2015
DOI: 10.1080/09613218.2015.1004150
|View full text |Cite
|
Sign up to set email alerts
|

Perceived control in indoor environments: a conceptual approach

Abstract: Building automation systems provide the potential to optimize the energy consumption of buildings as well as to detect failures in the operation of buildings. The system comprising building form-HVAC-building automation -user is becoming more complex. Providing the occupants with control over the indoor environment is widely accepted for its positive effect on their satisfaction. This paper explores what the term 'perceived control' means conceptually and draws implications for its application to the design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 23 publications
3
83
0
Order By: Relevance
“…Much adaptation involves changing the 'primary factors' in the heat balance equation, for instance wearing additional clothing when the temperature drops, but there is an additional psychological dimension (not included in the heat balance model) based on the occupants' perception of the opportunities available to control their conditions (Hellwig 2015) and on their expectations of typical or appropriate conditions (Nicol et al 2012). Oseland (1995) found that his British respondents chose (and reported feeling comfortable at) lower temperatures in their homes than in the office when the heat balance approach predicted the same comfort temperature in both locations.…”
Section: Thermal Comfortmentioning
confidence: 99%
“…Much adaptation involves changing the 'primary factors' in the heat balance equation, for instance wearing additional clothing when the temperature drops, but there is an additional psychological dimension (not included in the heat balance model) based on the occupants' perception of the opportunities available to control their conditions (Hellwig 2015) and on their expectations of typical or appropriate conditions (Nicol et al 2012). Oseland (1995) found that his British respondents chose (and reported feeling comfortable at) lower temperatures in their homes than in the office when the heat balance approach predicted the same comfort temperature in both locations.…”
Section: Thermal Comfortmentioning
confidence: 99%
“…The transient conditions around the occupants are demonstrated in the periodic distortion and reformation of the CBL. This interaction increases occupants perceived cooling of intermittent airspeeds and reduces the risk of the draft, giving a feeling of thermal pleasure or thermal alliesthesia in warm environments (Cabanac, 1971;Hellwig, 2015).Air movement acceptability and air quality acceptability are improved, especially under elevated room temperatures, which pave the way for energy-efficient cooling (Kabanshi et al, 2016b;Kabanshi et al, 2019). Applications and benefits: IAJS has been tested in a classroom mockup, which can be used as either an independent system that works as a primary ventilation system or as a room induction system (refer to schematic diagrams in Fig.…”
Section: Periodic Variation Of the Ventilation Flowrate With A Sinementioning
confidence: 99%
“…It is influenced by a great number of stimuli at once creating a complex net of relationships between mind, environment, and perception. The task of understanding how a given stimulus contributes to improving or impairing the state of mind of a person is very challenging [4] and it may even not be worth doing [5]. In an attempt to clarify the relationship between the built environment and human satisfaction, several interesting approaches have been developed (environmental determinism, social constructivism, and user-centered theories [6]), expanding the research to fields like medicine and psychology.…”
Section: Introductionmentioning
confidence: 99%